"Prison Ain't Free Like Everyone Thinks": Financial Stressors Faced by Incarcerated Women. (April 2017) - Harner, Holly M.; Wyant, Brian R.; Da Silva, Fernanda
Most women in prison are poor and suffer from health problems prior to and during incarceration. Policies that impose inmate medical co-payment fees do not consider gender-specific health needs or other financial stressors faced by women in prison. We examine the financial needs and concerns of incarcerated women through the lens of gender and behavioral economics. We conducted individual interviews with 95 women incarcerated in a medium/maximum security prison in the United States. Women described several common financial stressors during confinement: paying for medical care, "working for pennies, " staying in contact with loved ones, and relying on others. In an attempt to remain gender neutral, prison polices often do not consider gender-based differences between male and female prisoners. When gender neutrality is applied to financial policies surrounding access to healthcare, incarcerated women are profoundly disadvantaged and left to make consequential trade-offs with scarce financial resources. Our findings provide important insight into financial stressors facing incarcerated women and provide evidence to support the elimination of mandatory medical co-payment fees for incarcerated women.